Terrestrial laser scanning assessment of generalization errors in conventional topographic surveys - Sobak, Martin; Ellmann, Artu; Mill, Tarvo (Geodesy and Cartography, 2015)
The technology of terrestrial laser scanning has widely been used in the surveying industry in recent years due to higher data collecting productivity compared to traditional tacheometric survey. The aim of this study is to assess generalization errors in topographic surveys of landforms on the basis of a large vegetation free semi-coke landfill hill with the relative height of 116 m in North-East Estonia. The numerical assessment of errors is proceeded by comparing a high-resolution terrestrial laser scanning (TLS) 3D surface model with surface models generated from the sparser data steps (10, 20, 30 and 50 m). The 10 and 20 m data step surface models yield discrepancies within ± 20 cm. The 30 m data step models revealed slightly larger differences. Expectedly the largest elevation differences reaching up to 2.5 m were associated with the 50 m point step.